2000
DOI: 10.1086/309312
|View full text |Cite
|
Sign up to set email alerts
|

Accelerating Star Formation in Clusters and Associations

Abstract: We use our own, recently developed preÈmain-sequence evolutionary tracks to investigate the star formation histories of relatively nearby associations and clusters. We Ðrst employ published luminosities and e †ective temperatures to place the known members of each region in the H-R diagram. We then construct age histograms detailing that regionÏs history. The groups studied include Taurus-Auriga, Lupus, Chamaeleon, o Ophiuchi, Upper Scorpius, IC 348, and NGC 2264. This study is the Ðrst to analyze a large numb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

21
245
2

Year Published

2002
2002
2015
2015

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 253 publications
(268 citation statements)
references
References 111 publications
(115 reference statements)
21
245
2
Order By: Relevance
“…This means that the mass of star-forming dense gas increases A49, page 6 of 7 with the mass of the molecular cloud, and the star formation should accelerate over many million years. This conjecture may provide a clue to the star formation histories found by Palla & Stahler (2000) in seven individual molecular clouds such as Taurus-Auriga and ρ Ophiuchi. 8.…”
Section: Discussionmentioning
confidence: 74%
“…This means that the mass of star-forming dense gas increases A49, page 6 of 7 with the mass of the molecular cloud, and the star formation should accelerate over many million years. This conjecture may provide a clue to the star formation histories found by Palla & Stahler (2000) in seven individual molecular clouds such as Taurus-Auriga and ρ Ophiuchi. 8.…”
Section: Discussionmentioning
confidence: 74%
“…In young embedded clusters like the ONC, wide spreads in colour−magnitude diagrams (CMD) have been observed, which have previously been interpreted as age spreads of up to 10 Myr in association members (Palla & Stahler 2000). However, other authors have suggested that the observed CMD spreads are due to a mixture of photometric errors, variability in pre-MS stars (Herbst et al 1994), binarity (Preibisch & Zinnecker 1999), episodic accretion phases (Baraffe et al 2009), or a spread in line-of-sight distances or extinctions.…”
Section: Methodsmentioning
confidence: 99%
“…While the conclusion of Luhman (2007) that the star formation rate in Cha I has declined for several Myr already questions the scenario of Palla & Stahler (2000) in which star formation is a threshold phenomenon and accelerates as a result of cloud contraction (see Sect. 1), our findings raise new questions about the end of star formation.…”
Section: The End Of Star Formation In Cha I?mentioning
confidence: 99%
“…Based on the H-R diagram of the young stellar population known at that time (47 members with known spectral type), Palla & Stahler (2000) conclude that star formation in Cha I began within the last 7 Myr and that its rate steadily increased until recently. They find similar results in several other clouds and draw the general conclusion that star formation in nearby associations and clusters started slowly some 10 Myr ago and accelerated until the present epoch.…”
Section: Introductionmentioning
confidence: 97%